Miliary tuberculosis with co-existing pulmonary cryptococcosis in non-HIV patient without underlying diseases: a case report - Sawai, Toyomitsu (BMC Pulm Med, 2018)
BACKGROUND: Tuberculosis and cryptococcosis co-infection usually occurs in immunosuppressed patients with impaired cell-mediated immunity. However, there are few reports about such co-infection in non-HIV patients without underlying diseases. Here, we report a case of miliary tuberculosis with co-existing pulmonary cryptococcosis in non-HIV patient without underlying diseases. CASE PRESENTATION: An 84-year-old Asian female presented to our hospital with complaints of a 1-week history of abdominal pain and appetite loss. Chest computed tomography (CT) showed diffuse micronodules in random patterns in both lung fields. Liver, skin and bone marrow biopsies showed epithelioid cell granuloma. Polymerase chain reaction of gastric aspirate was positive for Mycobacterium tuberculosis. According to these findings, miliary tuberculosis was suspected and antimycobacterial therapy was initiated. After a 6-month treatment course, chest radiograph showed new multiple nodules in the right middle lung field. Chest CT showed that a right S6 small nodule was increased and new multiple nodules appeared in the right lower lobe. Flexible fiberoptic bronchoscopy was subsequently perfomed. Cytology of the bronchial lavage showed a small number of Periodic acid-Schiff-positive bodies, suggesting Cryptococcus species. Moreover, serum cryptococcal antigen testing was positive. According to these findings, pulmonary cryptococcosis was diagnosed, although the culture was negative. Oral fluconazole therapy was subsequently initiated. After a 6-month treatment course, chest radiograph showed gradual improvement. CONCLUSION: Although tuberculosis and cryptococcosis co-infection is relatively rare in immunocompromised hosts, such as those with acquired immunodeficiency syndrome, clinicians should be aware that these infections can co-exist even in non-HIV patients without underlying diseases.